2021
DOI: 10.1002/jac5.1477
|View full text |Cite
|
Sign up to set email alerts
|

Medication nonadherence monitoring and management in adult kidney transplantation: A survey of practices and perceptions at US‐based transplant programs

Abstract: Introduction: Medication nonadherence is a predominant contributor to graft loss, however little is known about currently utilized strategies by transplant centers to monitor or manage this issue.Objective: Utilizing standard surveying and analysis techniques, assess health care professionals' (HCPs) perceptions of the scope and scale of medication nonadherence and strategies used to manage this issue at US-based transplant centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Although the factors have been discussed, many studies still failed to evaluate how risk factors can be utilized to predict the risk of non-adherence behavior. A study conducted in 99 US-based transplant centers showed that 71.1% of health care professionals acknowledged not having a prospective medication non-adherence screening protocol, and little is known about strategies currently utilized by transplant centers to monitor or manage this issue (38). To solve this common problem, some scholars have attempted to establish predictive models of non-adherence in patients after kidney transplantation, such as HBM and TPB models (5,8,20,39).…”
Section: Discussionmentioning
confidence: 99%
“…Although the factors have been discussed, many studies still failed to evaluate how risk factors can be utilized to predict the risk of non-adherence behavior. A study conducted in 99 US-based transplant centers showed that 71.1% of health care professionals acknowledged not having a prospective medication non-adherence screening protocol, and little is known about strategies currently utilized by transplant centers to monitor or manage this issue (38). To solve this common problem, some scholars have attempted to establish predictive models of non-adherence in patients after kidney transplantation, such as HBM and TPB models (5,8,20,39).…”
Section: Discussionmentioning
confidence: 99%